Nano-enabled membranes technology: sustainable and revolutionary solutions for membrane desalination? - Goh, P. S. (Elsevier, 2016)
Multidisciplinary, innovative and high values development of high performance, cost-effective and environmentally acceptable separation systems is highly desired to tackle the sustainability challenges that facing current desalination technology. Owing to their versatility and immense potentials to evolve scientific and technical innovations, nanotechnology is probably one of the most prominent strategies that has gained growing scientific and public recognition to provide solutions that can extend the limits of sustainability in membrane desalination technology. This short review provides a brief insight into the roles and prospective of nanotechnology, particularly the nano-enabled membrane technology, to serve as a key element to render feasible solutions for sustainable development in membrane desalination technology. The contribution also highlights the strategies of transforming risk and challenges of this cutting edge technology into competitive advantage in order to timely and efficiently drive values in enhancing the desalination performance, profits and sustainability. The applications of nanomaterials and nanocomposite in membrane desalination are anticipated to foster untapped initiatives and innovation in fundamental science, engineering and technology to spearhead the new wave of leading edge sustainable membrane desalination technology.